Crown of midnight a Throne of glass novel - Maas, Sarah J (New York Bloomsbury, 2013)
As the royal assassin to an evil king, eighteen-year-old Celaena Sardothien must decide what she will fight for--survival, love, or the future of a kingdom
Sequel to: Throne of glass
Sequel: Heir of fire
1
Keywords: Assassins -- Fiction; Courts and courtiers -- Fiction; Fantasy; Kings, queens, rulers, etc -- Fiction; Love -- Fiction